VD_FINDINFO HC / 2017 / 1053 vom 4. Dezember 2017 - VD Tribunal cantonal (2017)
CONTRAT DE TRAVAIL, JUSTE MOTIF, RÉSILIATION IMMÉDIATE, INDEMNITÉEN GÉNÉRAL, DOMMAGES-INTÉRÊTS | 337c CO, 346 al. 2 CO, 355 CO